EKSISTENSI HUKUM SYARIAH ISLAM DI NANGGROE ACEH DARUSSALAM DITINJAU DARI KEKUASAAN KEHAKIMAN DI INDONESIA : The Existence of Islamic Sharia Law in Nanggroe Aceh Darussalam in Terms of Judicial Power in Indonesia - Afriza, Della; Sulistyowati, Tri (Faculty of Law, Universitas Trisakti, 2024)
The Existence of Islamic Sharia has an impact on the application of Judicial Power that apply Islamic Sharia Courts run by the Sharia Court. The Sharia Court is authorized to resolve cases at the first level and appeal level in the domains of family law, civil law and Islamic criminal law courtesy of Islamic Sharia. The matter of this assessment is how the existence of Islamic Sharia Law in Aceh viewed from the Judicial Power in Indonesia and how the consent of the Sharia Court in the special autonomy of Nanggroe Aceh Darussalam. This assessment uses secondary data obtained from literature and analyze qualitatively by using deductive logic inference. Courtesy of the analyze of this assessment, the existence of Sharia Law in Aceh courtesy of Undang-Undang Nomor 11 Tahun 2006 tentang Pemerintahan Aceh. Theses stipulations are intended for the population of Aceh who are Muslims and the authority of the Sharia Court in examining, judicating and deciding cases in cases of family law, civil law, Islamic criminal law in its implementation must not contradict national law especially the stipulations in the Civil Code, Criminal Code and Criminal Procedure Code.